PARTISIPASI MASYARAKAT DALAM PERLINDUNGAN HUKUM TERHADAP KEKAYAAN INTELEKTUAL WARISAN BANGSA - Endang Purwaningsih (Masalah-Masalah Hukum, 2012)
This article based on  research is to analyze the needs for community empowerment through sustainable participation approach concerning the protection of traditional knowledge and folklore. This folklore  essentially meets the requirements to be copyrighted;  the fact that it is a communal heritage property which has been passed on for generations and the creator is therefore not identified, cannot fulfill the requirement of originality and individuality.  The traditional knowledge that based on technology, yet it is not patentable invention, the fact that is not fulfill patentable requirement especially the novelty. Thus, traditional knowledge and folklore must be protected as 'sui generis' legal protection. Community empowerment program and community  legal awareness program should be done continually as well as progressing 'promote and protect' culture. The findings of this research suggest that indigenous people makers  need such supports as trainings, government's endorsement and incentives, capital provision schemes, as well as marketing and legal assistance. The findings also recommend that partnership between the traditional knowledge or folklore makers/indigenous people and the government be intensified to promote the product, not only locally, and nationally, but also internationally. This should involve the NGO, campus, the government, and related consultants to jointly protect this product and to help promote it in bigger scope.Keywords: community participation, promote and protect, traditional knowledge, folklore